Risk Assessment of the Carbon Nanotube Group. Issue 10 (5th May 2015) - Nakanishi, Junko; Morimoto, Yasuo; Ogura, Isamu; Kobayashi, Norihiro; Naya, Masato; Ema, Makoto; Endoh, Shigehisa; Shimada, Manabu; Ogami, Akira; Myojyo, Toshihiko; Oyabu, Takako; Gamo, Masashi; et al.
Abstract : This study assessed the health risks via inhalation and derived the occupational exposure limit (OEL) for the carbon nanotube (CNT) group rather than individual CNT material. We devised two methods: the integration of the intratracheal instillation (IT) data with the inhalation (IH) data, and the "biaxial approach." A four‐week IH test and IT test were performed in rats exposed to representative materials to obtain the no observed adverse effect level, based on which the OEL was derived. We used the biaxial approach to conduct a relative toxicity assessment of six types of CNTs. An OEL of 0.03 mg/m 3 was selected as the criterion for the CNT group. We proposed that the OEL be limited to 15 years. We adopted adaptive management, in which the values are reviewed whenever new data are obtained. The toxicity level was found to be correlated with the Brunauer‐Emmett‐Teller (BET)‐specific surface area (BET‐SSA) of CNT, suggesting the BET‐SSA to have potential for use in toxicity estimation. We used the published exposure data and measurement results of dustiness tests to compute the risk in relation to particle size at the workplace and showed that controlling micron‐sized respirable particles was of utmost importance. Our genotoxicity studies indicated that CNT did not directly interact with genetic materials. They supported the concept that, even if CNT is genotoxic, it is secondary genotoxicity mediated via a pathway of genotoxic damage resulting from oxidative DNA attack by free radicals generated during CNT‐elicited inflammation. Secondary genotoxicity appears to involve a threshold.